Coverage of gender roles in agriculture in four Nigerian newspapers (2000-2004) (2012)
Increasing roles of women in agricultural activities has made provision of gender responsive information imperative. This study investigated coverage of gender roles in agriculture in four selected Nigerian newspapers. Ninety-two articles representing the media coverage from four newspapers were coded for this study. Results indicated that the tabloids covered more non-gender stories (67.3%) than gender stories (32.6%), male roles enjoyed more prominence than female roles; and total amount of space allotted to females (51.3%) was more compared to male roles (48.7%). However, male roles (33.3%) in agricultural news coverage enjoyed more strategic placement as compared to female roles (23.3%), though space allotted (t = -0.16, p = 0.872) and placement (t = 0.94; p = 0.94) of male and female related stories were not significantly different. Civil society groups with mandates for agriculture and gender development should mount advocacy, mobilization and sensitization for media executives on the importance of gender responsive reporting of agricultural news.